2017
DOI: 10.12688/f1000research.12400.1
|View full text |Cite
|
Sign up to set email alerts
|

An international survey and modified Delphi process revealed editors’ perceptions, training needs, and ratings of competency-related statements for the development of core competencies for scientific editors of biomedical journals

Abstract: Background: Scientific editors (i.e., those who make decisions on the content and policies of a journal) have a central role in the editorial process at biomedical journals. However, very little is known about the training needs of these editors or what competencies are required to perform effectively in this role. Methods: We conducted a survey of perceptions and training needs among scientific editors from major editorial organizations around the world, followed by a modified Delphi process in which we invit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…This omission from the CC is surprising, especially since plagiarism featured in two of the 23 highly ranked statements in the Delphi process 2 . While working with authors on manuscripts, authors’ editors sometimes encounter re-used text and inadequate citation, and use these opportunities to explain why these practices may be inappropriate and how to avoid them 25 .…”
Section: Correspondencementioning
confidence: 99%
See 2 more Smart Citations
“…This omission from the CC is surprising, especially since plagiarism featured in two of the 23 highly ranked statements in the Delphi process 2 . While working with authors on manuscripts, authors’ editors sometimes encounter re-used text and inadequate citation, and use these opportunities to explain why these practices may be inappropriate and how to avoid them 25 .…”
Section: Correspondencementioning
confidence: 99%
“…Meanwhile, biomedical journals publish an ever-increasing proportion of articles that were judged by reviewers to have “acceptable English” but which contain awkwardly worded statements that defy comprehension and undermine reproducibility 2(pp5–9) . To avoid these problems, journal editors should be able to either provide authors with useful feedback on the language (e.g.…”
Section: Correspondencementioning
confidence: 99%
See 1 more Smart Citation
“…An article closely related to the one we commented on had been published (Galipeau et al 2017) earlier on F1000Research, an innovative open-access, open-peer review publishing platform where peer review begins after publication; when two reviewers have approved the manuscript, it is indexed in bibliographic databases. The platform's Editorial Director was among the authors of both the earlier related article and the more recent BMC Medicine article we discussed, so we hoped that F1000Research would give our manuscript a respectful reading (M.E.…”
Section: Third Venuementioning
confidence: 99%
“…Readers have the right to expect that they do their utmost best to implement all reasonable standards to ensure the quality of the articles that are published in the journal. Interestingly, not much evidence is available what competencies editors should have to meet these standards . Through a scoping review competencies for editors were identified and these were then developed further through a modified Delphi procedure for which editors through major editorial organizations such as the World Association of Medical Editors (WAME) and Committee on Publication Ethics (COPE) were invited.…”
mentioning
confidence: 99%